Electric Field as A Novel Switch to Enhance Optical Absorption Spectra of Defect Blue Phosphorene Thin-films - Duy, Nguyen Vo Anh; Triet, Dang Minh; An, Dinh Van (VNU Journal of Science: Mathematics - Physics, 2022)
Improvement of the optical absorption coefficient is essential to enhance the light conversion efficiency of thin-film organic solar cells. Here we report the use of an external electric field as a novel switch to improve the optical absorption capacity of two-dimensional defect blue phosphorene (BlueP) systems. Using the density functional theory with van der Waals functionals, we investigate the structural, electronic, magnetic and optical absorption properties of the pristine, single-vacancy (SV) BlueP thin films, and a BlueP system absorbing a Vanadium adatom. We demonstrate that a SV BlueP layer would exhibit half-metallic and its absorption spectrum under an electric field parallel to the material plane is significantly enhanced in the ultra-violet region. More interestingly, when a Vanadium transition metal is absorbed on a pristine BlueP, the applied electric field perpendicular to the BlueP plane not only doubles the optical absorption coefficient, but also switches ON/OFF the magnetic moments of this system. The prominent red shift of the absorption spectra towards the visible light range under selected polarized directions paves a novel way to engineer solar cell devices with BlueP materials.